A BIBLIOMETRIC ANALYSIS OF HUMAN RESOURCE DEVELOPMENT RESEARCH: TRENDS AND RESEARCH FOCUS FROM 2010 TO 2023 - Suryana, R.E (Universitas Pendidikan Indonesia, 2024)
This research has the main objective of uncovering trends and research focus in the context of human resource development, using a bibliometric analysis approach, during the period 2010 to 2023. The dataset used comes from the Scopus platform and includes 817 publication metadata relevant to the topic under study. By applying the keywords